Teacher voice: how is it shaped? - Becerra Camargo, Claudia Yolanda (Colombian Applied Linguistics Journal, 2005)
This article aims at being an invitation for the readers to refl ect upon the way in which our voices as teachers are shaped. My own refl ective process geared me towards the characterization of three key issues which –from my personal and professional experience- shape teacher voice. They are: the political relations of power, the curricular choices we make and their implications, and the government policies. Grounded on some Critical Pedagogy scholars, I defi ne fi rst, Critical pedagogy from my personal stand. Second, I present the defi nition of teacher voice, from different perspectives, including mine. Third, I describe and illustrate each of the three central features that may shape our voices as teachers and fi nally, I state some conclusions and pedagogical implications.